2014
DOI: 10.1152/japplphysiol.01535.2012
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary surfactant synthesis after unilateral lung injury in mice

Abstract: Aspiration pneumonitis can lead to alveolar surfactant dysfunction. We employed a murine model of unilateral aspiration to compare surfactant synthesis in the injured (I) and noninjured (NI) contralateral lung. Mice were instilled with hydrochloric acid in the right bronchus and, after 18 h, an intraperitoneal dose of deuterated water was administered as precursor of disaturated phosphatidylcholine (DSPC)-palmitate. Selected bronchoalveolar lavage fluid (BALF) was collected at scheduled time points and lungs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…Finally, it is possible that the excess of SP-B may reflect an accumulation of surfactant subfractions particularly enriched in SP-B (19). The decrease of the SP-B (%PL) ratio along with clinical and respiratory improvements, were reasonably related with a better oxygenation status, which may represent the result of an improved clearance or a decreased secretion of SP-B.Our data are in line with previous results obtained both in animal studies (20,21) and in newborns after lung injury (22,23). Ikegami et al (20) found that in healthy mice (with normal lungs) the induction of lung injury by the intratracheal injection of LPS resulted in an increase of DSPC and SP-B, mediated by STAT-3, which is consistent with an acute response to the lung injury.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Finally, it is possible that the excess of SP-B may reflect an accumulation of surfactant subfractions particularly enriched in SP-B (19). The decrease of the SP-B (%PL) ratio along with clinical and respiratory improvements, were reasonably related with a better oxygenation status, which may represent the result of an improved clearance or a decreased secretion of SP-B.Our data are in line with previous results obtained both in animal studies (20,21) and in newborns after lung injury (22,23). Ikegami et al (20) found that in healthy mice (with normal lungs) the induction of lung injury by the intratracheal injection of LPS resulted in an increase of DSPC and SP-B, mediated by STAT-3, which is consistent with an acute response to the lung injury.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, our research group observed how, in a murine model of unilateral lung injury, DSPC-palmitate synthesis was faster both in the injured and in the noninjured lungs, compared to the naïve control lungs. In this way we proved that, after a local instillation of acid in one bronchus, it is the entire lung system that is involved in responding to the damage and not only a local area of the lung (21). Other mechanisms may have contributed to the elevation of SP-B levels.…”
Section: Discussionmentioning
confidence: 62%
“…Albumin concentration was measured with the bromocresol green method (21). MPO was measured as reported previously (22).…”
Section: Sample Analysismentioning
confidence: 99%
“…This adverse change can be attributed to pulmonary oedema due to the increased vascular permeability (Goldman et al, 1993;Grimbert et al, 1981;Ko et al, 2008), surfactant dysfunction (Davidson et al, 2005;Lamonica et al, 2014) and inflammation (Knight et al, 1992;Nader-Djalal et al, 2007). Since all of these processes promote the development of atelectasis leading to a lung volume loss, the elevations in the unilateral G and H in the aspirated lungs are likely to occur subsequently to this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Another direct effect of gastric juice aspiration may be related to pepsin being cytotoxic to bronchial epithelial cells (Bathoorn et al, 2011). A further direct mechanism of lung injury following bronchoaspiration may be subsequent to the induced surfactant dysfunction (Lamonica et al, 2014). Besides these direct mechanisms, indirect pathways have also been reported to be involved in the course of aspiration, since the lung injury has been found to be mediated by capsaicin-sensitive vagal sensory afferent nerves (Kennedy et al, 1989;Kollarik et al, 2007;Martling and Lundberg, 1988;Nemzek and Kim, 2009).…”
Section: Introductionmentioning
confidence: 99%